2015
DOI: 10.1007/s11892-015-0656-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Type 1 Diabetes-Associated IFIH1 Polymorphisms on MDA5 Function and Expression

Abstract: Recent evidence has highlighted the role of the innate immune system in type 1 diabetes (T1D) pathogenesis. Specifically, aberrant activation of the interferon response prior to seroconversion of T1D-associated autoantibodies supports a role for the interferon response as a precipitating event toward activation of autoimmunity. Melanoma differentiation-associated protein 5 (MDA5), encoded by IFIH1, mediates the innate immune system's interferon response to certain viral species that form double-stranded RNA (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 70 publications
3
38
0
Order By: Relevance
“…We have developed a cell-based assay to study recombination of EV-A71 based upon previously reported assays for poliovirus recombination. Our results show that: (1) EV-A71 strain-type and RNA sequence diversity impacts recombination frequency in a predictable manner that mimics the observations found in nature; (2) recombination is primarily a replicative process mediated by the RNA-dependent RNA polymerase (RdRp); (3) a mutation shown to reduce recombination in PV (L420A) similarly reduces EV-A71 recombination suggesting conservation in mechanism(s); and (4) sequencing of intertypic recombinant genomes indicates that template-switching is by a mechanism that requires some sequence homology at the recombination junction and that the triggers for template-switching may be sequence independent. The development of this recombination assay will permit further investigation on the interplay between replication, recombination and disease.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…We have developed a cell-based assay to study recombination of EV-A71 based upon previously reported assays for poliovirus recombination. Our results show that: (1) EV-A71 strain-type and RNA sequence diversity impacts recombination frequency in a predictable manner that mimics the observations found in nature; (2) recombination is primarily a replicative process mediated by the RNA-dependent RNA polymerase (RdRp); (3) a mutation shown to reduce recombination in PV (L420A) similarly reduces EV-A71 recombination suggesting conservation in mechanism(s); and (4) sequencing of intertypic recombinant genomes indicates that template-switching is by a mechanism that requires some sequence homology at the recombination junction and that the triggers for template-switching may be sequence independent. The development of this recombination assay will permit further investigation on the interplay between replication, recombination and disease.…”
supporting
confidence: 68%
“…This group of viruses, typified by poliovirus, has a 7.5 kb positive-sense RNA genome that encodes a single polyprotein that is flanked by non-coding regions (NCR). The polyprotein is co- and post-translationally processed by virus-encoded proteases to generate the structural proteins (VP4, VP2, VP3 and VP1), which assemble to form the icosahedral capsid and the non-structural proteins (2A pro , 2B, 2C, 3A, 3B VPg , 3C pro and 3D pol ) that mediate replication of the virus genome (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in IFIH1 are associated with T1D. [10, 11]. Enterovirus, especially coxsackievirus B (CVB) [12], have a tropism for pancreatic β cells, and persistent CVB infection of β cells is detected in 60–70% of pancreases from T1D individuals compared to only 6% in non-diabetic individuals [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we described that this relatively common polymorphism is associated with T1DM both in the high‐incidence Finnish and medium‐incidence Hungarian populations (G allele [vs A allele] was significantly associated with the decreasing risk of T1DM [odds ratio 0.81 with 95% confidence interval CI of 0.71‐0.92]) . Other investigations and meta‐analyses also indicated that an association between IFIH1 rs1990760 polymorphism and T1DM exists and carriers of the minor G allele might truly have a modest protection for T1DM, primarily in the Caucasian population . The exact mechanism of the observed association has remained to be determined so far …”
Section: Introductionmentioning
confidence: 94%
“…9 Other investigations and meta-analyses also indicated that an association between IFIH1 rs1990760 polymorphism and T1DM exists and carriers of the minor G allele might truly have a modest protection for T1DM, primarily in the Caucasian population. [10][11][12][13][14] The exact mechanism of the observed association has remained to be determined so far. 15,16 Undoubtedly, the genetic architecture of T1DM is complex and, besides IFIH1 polymorphisms, other gene variants may contribute to diabetes manifestation.…”
Section: Introductionmentioning
confidence: 99%